Multiliterasi: Pilihan Terbaik dalam Pembelajaran Cerita Pendek - Agung Nasrulloh Saputro (Journal on Education, 2023)
This article discusses the importance of learning short stories in a multiliteracy perspective. As a multiliteracy learning model that is able to stimulate and develop student creativity. This study aims to critically describe the current obstacles to learning short stories in the Indonesian language and literature education study program at the Madiun Residency, the weaknesses and opportunities for improvement with the multiliteracy learning model. This study uses a qualitative form with a descriptive-interpretative approach. This approach is considered capable of describing opinions or views that exist in the object of research. The results of this study include: 1) learning short stories in the Indonesian language and literature education study program at the Madiun Residency currently has several obstacles, namely the unbalanced literature courses in the curriculum in the Indonesian language and literature education study program at the Madiun Residency, 2 ) students' interest in literature courses, especially writing short stories, is very low which is influenced by student background factors, view factors of learning literature, especially poetry, are not important, and the low culture of reading literature for students, and 3) the need for a multiliteracy learning model from interview data illustrates that teaching staff really need learning models that are new, practical, and easy to understand.